Biomass vs inorganic and plastic-based aerogels: Structural design, functional tailoring, resource-efficient applications and sustainability analysis. (April 2022) - Wei, Gang; Zhang, Jianming; Usuelli, Mattia; Zhang, Xiaofang; Liu, Bin; Mezzenga, Raffaele
Graphical abstract: Biomass-based aerogels with tailored structure and functions exhibited resource-efficient applications and high sustainability. Abstract: The highly efficient utilization of bioresources and natural organic wastes has attracted great attention, due to the high-speed consumption and shortage of energy in modern society. Aerogels, attributable to their outstanding properties and potential applications in diverse fields, have been a major topic of innovative materials research in the last decades. While previously the scientific community has mainly focused on inorganic- and plastic-based aerogels, recent years have witnessed a growing interest in their biomass-based counterparts. In fact, numerous studies on the fabrication, modification, and applications of cellulose, polysaccharide, protein, peptide, and other bio-derived aerogels have been widely reported. In this review, we focus on recent advances in the biomass-based aerogels field. The analysis that we perform ranges from their structural design to routes for functional tailoring, and encompasses resource-efficient applications; the aim is to provide a comprehensive review based on a robust analysis of available data. The fabrication techniques, structure and properties of biomass-based aerogels are introduced, together with their chemical, mechanical, electrical, optical, and biological properties. In addition, the structural design, functional tailoring, and applications of biomass-based aerogels are demonstrated. Furthermore, we enrich the actual literature state-of-the-art with a broad sustainability analysis, that compares biomass-based aerogels to the most studied inorganic/plastic-based counterparts. To this end, we perform a comparison with inorganic- and plastic-based aerogels by sustainability footprint analysis, which accounts for 12 sustainability parameters on environmental, social, and techno-economic impacts. This review will guide readers in understanding the fabrication of biomass-based aerogels, together with their structural and functional adjustment, through comprehensively presenting the state-of-the-art on their sustainable applications in fields as diverse as biomedical engineering, energy materials, nanodevices, chemical engineering, and environmental science.